2013
DOI: 10.1007/s10534-013-9670-y
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of manganese transport and gene expressions of manganese transport carriers in Caco-2 cell monolayers

Abstract: Two experiments were conducted to investigate the kinetics of manganese (Mn) transport in Caco-2 cell monolayers and the gene expressions of Mn transport carriers in apical (AP) and basolateral (BL) membranes. In experiment 1, the cells were treated with the medium containing 146 μmol/L of Mn (MnSO4·H2O). Both the uptake and transport of Mn from AP-BL or from BL-AP at different time-points were assessed to determine the optimal time for kinetics of Mn transport. The transport of Mn increased linearly with high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…For example, inducible expression of Fpn in HEK293T cells reduces Mn accumulation and toxicity (26). Kinetic studies in Caco-2 cell monolayers, an in vitro model for intestinal absorption, also support a role for Fpn in basolateral export of Mn (41). However, more recent studies in Xenopus oocytes injected to express Fpn demonstrated efflux of 55 Fe, 65 Zn, and 57 Co but not 64 Cu, 109 Cd, or 54 Mn (25).…”
Section: Discussionmentioning
confidence: 99%
“…For example, inducible expression of Fpn in HEK293T cells reduces Mn accumulation and toxicity (26). Kinetic studies in Caco-2 cell monolayers, an in vitro model for intestinal absorption, also support a role for Fpn in basolateral export of Mn (41). However, more recent studies in Xenopus oocytes injected to express Fpn demonstrated efflux of 55 Fe, 65 Zn, and 57 Co but not 64 Cu, 109 Cd, or 54 Mn (25).…”
Section: Discussionmentioning
confidence: 99%
“…37 Studies of manganese transfer across Caco-2 cell monolayers, an in vitro model for intestinal absorption, are consistent with DMT1 and Fpn mediating apical uptake and basolateral export of manganese. 38 In other studies, inducible expression of Fpn in HEK293T cells reduced manganese accumulation and toxicity. 39 Treatment with manganese 40,41 and other metals 42 has been shown to regulate Fpn expression.…”
Section: Ferroportin (Slc40a1)mentioning
confidence: 87%
“…39 Treatment with manganese 40,41 and other metals 42 has been shown to regulate Fpn expression. In macrophages, Fpn expression is altered by exposure to manganese, 43 Hepcidin is also present in alveolar macrophages, 38,44 but the possible role for Fpn in manganese transport, its speculative function in the respiratory uptake of the metal and/or its detoxification, and the potential role for hepcidin in the regulation of these processes remain to be fully explored.…”
Section: Ferroportin (Slc40a1)mentioning
confidence: 99%
“…Several organic forms of dietary Mn including metal‐amino acid complexes had been developed as dietary Mn supplements in poultry and livestock. Several studies demonstrated that Mn‐amino acid complex was more bioavailable than inorganic Mn sulphate, using ligated chicken intestinal loop (Bai et al., , ) and Caco‐2 cell models (Li et al., ). Others reported no differences in Mn bioavailability between organic and inorganic Mn sources (Baker and Halpin, ; Scheideler, ).…”
Section: Introductionmentioning
confidence: 99%